Arilsulfatasa en la rizosfera de plátano, Musa AAB y relación con crecimiento, desarrollo y producción - Bolaños Benavides, Martha M.; Sánchez de Prager, Marina; Rao, Idupulapati M. (2006)
Arylsulphatase in the rhizosphere of plantain Musa AAB and its relation with growth, development and production. In a plantain crop (Musa AAB) of the Central coffee growing zone of Colombia, arylsulphatase activity in a Pachic Melanudand Medial Isotermic soil under three agronomic management systems during 18 months was measured. Measurements were done at 6, 12 and 18 months in four depths, 0-5, 5-10, 10-20, 20-30 cm. The highest arylsulphatase activity (60%) was found in the ?rst 10 cm, with a decreasing in depth. Statical analysis did not show signi?cant differences among the three plant ages. Arylsulphatase activity was found between 164 µmol g-1 min-1 and 319 µmol g-1 min-1. The lowest activity was found in the rhizosphere of plants with 12 months of age (?owering) under chemical management. Arylsulphatase activity showed very signi?cant correlation with Biomass-C and with Mg in soil, number of leaf and the plantain bunch weight.